Short Communication: Detection of lectin gene (MLL1 and M35) in mulberry plant (Morus spp.) from Bogor, West Java, Indonesia - YASINTA RATNA ESTI WULANDARI; YOGIARA YOGIARA; MICHAEL LIZAR (Biodiversitas Journal of Biological Diversity, 2018)
Wulandari YRE, Yogiara, Lizar M. 2018. Short Communication: Detection of lectin gene (MLL1 and M35) in mulberry plant (Morus spp.) from Bogor, West Java, Indonesia Biodiversitas 19: 2381-2384. Plant species contains carbohydrate-binding protein known as lectin or agglutinin. Lectin binds to specific carbohydrates, such as monosaccharides or oligosaccharides and initiates agglutination process. Lectin plays an important role as plant defense, so that it can be used to prevent pest attacks. Mulberry leaf lectin 1 (MLL1) from young leaves of Morus alba can be used against phytopathogenic bacteria, Pseudomonas syringae pv. mori. Mannose-binding lectin (M35) was found on stems of M. nigra as protein storage. M35 is also produced on roots of M. alba and induced by mulberry stem cuttings. This research purpose was to isolate and analyze lectin gene expression (MLL1 and M35) in M. alba var. multicaulis, M. cathayana, M. bombycis var. lembang, and M. alba var. kanva-2 from Bogor, West Java, Indonesia. Different plant organ including leaves, stems, and roots were used as source of samples and analyze using Reverse Transcription Polymerase Chain Reaction (RT-PCR). Our results showed that all of MLL1 genes were expressed in young leaves, but not expressed in stems and roots of mulberry plant samples. The M35 gene was expressed in young leaves, stems, and roots of all mulberry plant samples. Reverse Transcription PCR of MLL1 gene exhibited a 350 bp DNA band, while M35 gene exhibited a 99 bp DNA band.